Video Head Impulse Test Findings in Patients With Benign Paroxysmal Positional Vertigo Secondary to Idiopathic Sudden Sensorineural Hearing Loss - Liu, Yingzhao; Leng, Yangming; Zhou, Renhong; Liu, Jingjing; Wang, Hongchang; Xia, Kaijun; Liu, Bo; Xiao, Hongjun (Frontiers in Neurology, 2022)
Benign paroxysmal positional vertigo (BPPV) is the most common cause of episodic vestibular syndrome. It can be classified as idiopathic and secondary types according to the causative factors, and the underlying mechanism between idiopathic (i-BPPV) and secondary BPPV (s-BPPV) may differ. Idiopathic sudden sensorineural hearing loss (ISSNHL) has been considered as a common inner ear disease that precipitates s-BPPV. Yet few study has addressed the functional impairment in semicircular canal (SCC) system in patients with s-BPPV associated with ISSNHL. Our purpose was to explore the pathophysiological mechanism and investigate the clinical implications of vHIT in these patients. Here, the clinical and laboratory data of patients with BPPV secondary to ISSNHL, including the results of video head impulse test (vHIT), were retrospectively reviewed, and compared with those of patient with i-BPPV. Pathological vHIT findings (low VOR gain and re-fixation saccade), which mainly affected the posterior SCC, were more common in the s-BPPV group than those in the i-BPPV group (41.9% and 0, respectively). The incidence of horizontal SCC involvement was also higher in s-BPPV group (45.16% and 16.67%, respectively). Furthermore, s-BPPV patients showed lower vHIT gains of the posterior and horizontal SCCs in the affected ears than in the non-affected ears. Compared to idiopathic BPPV, posterior SCC paresis detected by vHIT is more prevalent in BPPV secondary to ISSNHL. This dysfunction may be associated mainly with vestibular impairments caused by ISSNHL, not BPPV per se.